Review on the physical chemistry of iodine transformations in the oceans - Luther, George W. (Frontiers in Marine Science, 2023)
The transformation between iodate (IO3−), the thermodynamically stable form of iodine, and iodide (I-), the kinetically stable form of iodine, has received much attention because these species are often dependent on the oxygen concentration, which ranges from saturation to non-detectable in the ocean. As suboxic conditions in the ocean’s major oxygen minimum zones indicate that IO3− is minimal or non-detectable, the incorporation of IO3− into carbonate minerals has been used as a redox proxy to determine the O2 state of the ocean. Here, I look at the one and two electron transfers between iodine species with a variety of oxidants and reductants to show thermodynamics of these transformations. The IO3− to IO2− conversion is shown to be the controlling step in the reduction reaction sequence due to thermodynamic considerations. As IO3− reduction to IO2− is more favorable than NO3− reduction to NO2− at oceanic pH values, there is no need for nitrate reductase for IO3− reduction as other reductants (e.g. Fe2+, Mn2+) and dissimilatory IO3− reduction by microbes during organic matter decomposition can affect the transformation. Unfortunately, there is a dearth of information on the kinetics of reductants with IO3−; thus, the thermodynamic calculations suggest avenues for research. Conversely, there is significant information on the kinetics of I- oxidation with various oxygen species. In the environment, I- oxidation is the controlling step for oxidation. The oxidants that can lead to IO3− are reactive oxygen species with O3 and •OH being the most potent as well as sedimentary oxidized Mn, which occurs at lower pH than ocean waters. Recent work has shown that iodide oxidizing bacteria can also form IO3−. I- oxidation is more facile at the sea surface microlayer and in the atmosphere due to O3.